Fall or Rise? Mapping the Development of Traditional and Digital Newspapers - Muhammad Ramzan Pahore; Sumera Memon; Qaiser Khan (Progressive Research Journal of Arts & Humanities (PRJAH), 2021)
Daily newspapers in the world are shrinking in many dimensions. All big or small newspapers are getting smaller in size, business and news circulation. The speed at which newspapers are shutting down is not much different from the early 20th century. Thus, most newspapers are shifting from conventional setting to online/ digital newspapers only. Since the last two decades, the business of newspaper has declined as many newspapers have migrated business and appearance online to retain print readers via online only consumers and attract new ones who are just netters in the world. This change has been noticed in all countries. Pakistan is also one among those countries in which new technology is being adopted in the field of media. Due to information communication technologies, most of the Pakistani print, electronic media organization has switched to online to keep pace with the developed world. Hence, most of the conventional/traditional newspapers become digital newspapers along with print publications. Therefore, this paper discusses the history and development of online newspapers. Digital media has the power to attract many young news consumers because of its convenience, ease of excess, update 24/7 and availability at any time. These features are the prime source of newspaper decline and a major source of digital media growth.